QCM sensor and preparation method and application thereof

By setting the fullerol/Ti3C2Tx composite film on the high fundamental frequency QCM substrate of the QCM humidity sensor, the problem of low humidity sensitivity caused by Ti3C2Tx self-stacking is solved, and higher humidity sensitivity response performance and faster response/recovery characteristics are achieved.

CN119510209APending Publication Date: 2025-02-25SOUTHWEST JIAOTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411656326.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing QCM humidity sensor based on Ti3C2Tx is easy to self-stack, which limits the diffusion of water molecules in the thin film, resulting in low humidity sensitivity and response of the sensor.

Method used

A fullerol/Ti3C2Tx composite film is installed on a high-brain frequency QCM substrate, and the layered structure is stabilized by uniform dispersion of fullerol and hydrogen bonding, the layer spacing is expanded, the self-stack of Ti3C2Tx is inhibited, and the hydrophilicity of the composite film is improved.

Benefits of technology

It significantly enhances the diffusion ability of water molecules in the composite film, improves the moisture-sensitive response performance of the sensor, reduces the moisture-hysteresis effect, and achieves rapid response/recovery characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119510209A_ABST
    Figure CN119510209A_ABST
Patent Text Reader

Abstract

The invention discloses a QCM sensor and a preparation method and application thereof, and belongs to the technical field of humidity sensors. According to the invention, the problem of low humidity-sensitive responsivity of the sensor caused by easy self-stacking of Ti3C2Tx is solved. In the fullerol / Ti3C2Tx composite film, the fullerol is uniformly dispersed on the surface of the Ti3C2Tx and among layers of the Ti3C2Tx, and hydroxyl groups on the fullerol and functional groups on the surface of the Ti3C2Tx form hydrogen bonds, so that the layered structure of the fullerol and the Ti3C2Tx is stabilized, the self-stacking phenomenon of the Ti3C2Tx is remarkably inhibited, and the diffusivity of water molecules in the composite film is enhanced. The hydrophilicity of the composite film is remarkably improved by rich hydroxyl functional groups in the fullerol, and the sensitivity of the sensor is further enhanced. According to the sensor, a high-fundamental-frequency patch type high-fundamental-frequency QCM substrate is used as a transducer, excellent humidity-sensitive response can be achieved only through a trace amount of humidity-sensitive materials, the small humidity hysteresis effect and the rapid response / recovery characteristic are shown, and the sensor can be applied to the field of palm and hand back monitoring and can be used for accurately distinguishing the palm and the hand back.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of humidity sensors, and in particular relates to a QCM sensor and a preparation method and application thereof. Background Art

[0002] Humidity sensors, as key components for monitoring humidity, play a vital role in many fields such as environmental monitoring, medical health, industrial control and agriculture. Among the many types of humidity sensors, humidity sensors based on quartz crystal microbalance (QCM) have received special attention due to their ability to provide digital frequency output.

[0003] At present, an article titled "Controllable preparation of titanium carbide MXene nanosheets and their excellent QCM humidity sensing properties enhanced by fluoride doping" in Microchimica Acta publicly proposed a QCM humidity sensor based on titanium carbide MXene nanosheets (Ti3C2Tx) film. However, since Ti3C2Tx is easy to self-stack, it limits the diffusion of water molecules in the film, which in turn leads to a lower humidity sensitivity response of the sensor. Summary of the invention

[0004] In view of the problem in the prior art that Ti3C2Tx is easy to self-stack, which limits the diffusion of water molecules in the film and thus leads to low humidity sensitivity of the sensor, the present invention provides a QCM sensor and a preparation method and application thereof.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A QCM sensor comprises a high fundamental frequency QCM substrate, wherein the high fundamental frequency QCM substrate comprises a quartz wafer and an upper electrode layer and a lower electrode layer respectively arranged on the upper and lower surfaces of the quartz wafer, wherein a fullerol / Ti3C2Tx composite film is arranged on the surface of the upper electrode layer, and fullerol is dispersed on the surface and between Ti3C2Tx in the fullerol / Ti3C2Tx composite film.

[0007] After adopting this technical solution, a fullerol / Ti3C2Tx composite film is arranged on a high fundamental frequency QCM substrate in the present invention. In the fullerol / Ti3C2Tx composite film, the fullerol is uniformly dispersed on the surface of Ti3C2Tx and between the layers of the adjacent Ti3C2Tx films, and the hydroxyl groups thereon form hydrogen bonds with the surface functional groups of Ti3C2Tx. These hydrogen bonds further stabilize the layered structure of fullerol and Ti3C2Tx, thereby effectively expanding the interlayer spacing and reducing the interlayer van der Waals force, thereby significantly inhibiting the self-stacking phenomenon of Ti3C2Tx and enhancing the diffusion capacity of water molecules in the composite film. In addition, the rich hydroxyl functional groups in fullerol significantly improve the hydrophilicity of the composite film, further enhancing the sensitivity of the sensor. The high fundamental frequency QCM substrate of the sensor is used as a transducer, and only a trace amount of hygroscopic material is required to achieve excellent hygroscopic response. At the same time, the sensor exhibits a small hygroscopic effect and fast response / recovery characteristics.

[0008] Preferably, the connection relationship between the materials in the fullerol / Ti3C2Tx composite film is that fullerol is dispersed on the surface and between the Ti3C2Tx sheets.

[0009] Preferably, the fullerol particle size in the fullerol / Ti3C2Tx composite film is 1-100 nm, and the number of hydroxyl groups is 15-40.

[0010] After adopting this technical solution, fullerol with a hydroxyl number of 15 to 40 is selected to prepare Ti3C2Tx / fullerol composite film, so that the obtained fullerol / Ti3C2Tx composite film has both excellent hydrophilicity and water solubility, and avoids the molecular structure instability caused by too high a hydroxyl number.

[0011] Preferably, the number of Ti3C2Tx layers in the fullerol / Ti3C2Tx composite film is 1 to 5, and the sheet diameter is 0.2 to 10 μm.

[0012] After adopting this technical solution, the Ti3C2Tx film with fewer layers is conducive to the diffusion of water molecules. At the same time, the moderate sheet diameter provides a larger specific surface area, thereby increasing the adsorption sites of the composite film for water molecules.

[0013] Preferably, the high fundamental frequency QCM substrate is a patch type QCM, and the reference frequency is 15MHz to 40MHz.

[0014] After adopting this technical solution, a high fundamental frequency patch QCM is used as a transducer, and only a trace amount of humidity-sensitive material is needed to achieve excellent humidity-sensitive response, and exhibit a small hysteresis effect and fast response / recovery characteristics.

[0015] A method for preparing a QCM sensor, comprising:

[0016] S1: Preparation of fullerol / Ti3C2Tx composite dispersion solution;

[0017] S2: The prepared fullerol / Ti3C2Tx composite dispersion solution is coated on the surface of the high fundamental frequency QCM substrate to form a fullerol / Ti3C2Tx composite film to obtain a QCM sensor.

[0018] Preferably, the specific steps of S1 are as follows:

[0019] S11: preparing a fullerol solution with a concentration of 0.1 to 10 mg / mL by mixing fullerol powder with water;

[0020] S12: preparing a Ti3C2Tx solution with a concentration of 0.1 to 10 mg / mL by mixing Ti3C2Tx powder with water;

[0021] S13: The Ti3C2Tx solution and the fullerol solution are mixed in a mass ratio of 1:(0.01-10) to form a fullerol / Ti3C2Tx composite dispersed solution with a concentration of 0.1-10 mg / mL.

[0022] Preferably, the coating method is any one of drop coating, spin coating and spray coating.

[0023] Preferably, the amount of the Ti3C2Tx / fullerol composite dispersion solution is 0.0125-0.125 μL / mm 2 , and the amount of fullerol / Ti3C2Tx composite dispersion solution increases with the increase of the surface area of ​​the high fundamental frequency QCM substrate.

[0024] The invention discloses an application of a QCM sensor in identifying the palm and back of a hand wearing a glove.

[0025] After adopting this technical solution, the ultra-sensitive QCM humidity sensor can detect the evaporation of sweat in the palm and back of the hand wearing the glove, and then identify the palm and back of the hand by distinguishing the difference between the two evaporation conditions. Compared with vision-based sensors, the QCM humidity sensor mentioned in the present invention is less sensitive to ambient light fluctuations during the recognition process, so the recognition ability is more stable in an environment with complex and changeable light.

[0026] Preferably, the gloves are breathable gloves.

[0027] As a preference, the method comprises the following steps:

[0028] A1: Place the QCM sensor close to the palm and back of the hand where the gloves are worn;

[0029] A2: The QCM sensor is used to detect the evaporation of sweat from the palm and back of the hand wearing the glove, and the palm and back of the hand are identified by distinguishing the difference in sweat evaporation.

[0030] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:

[0031] The present invention arranges a fullerol / Ti3C2Tx composite film on a high fundamental frequency QCM substrate. The fullerol / Ti3C2Tx composite film contains fullerol with an appropriate number of hydroxyl groups, which has excellent hydrophilicity and water solubility, and avoids the instability of the molecular structure caused by too high a number of hydroxyl groups. In addition, the uniform distribution of fullerol on the surface of Ti3C2Tx and its ingenious embedding between the layers form a strong "molecular anchor chain" through hydrogen bonds, which greatly enhances the binding force between the two. At the same time, these intercalated fullerols construct a microscopic "nano-scaffold" structure. This structure effectively widens the Ti3C2Tx interlayer spacing (between adjacent Ti3C2Tx and Ti3C2Tx), suppresses the self-stacking phenomenon of Ti3C2Tx caused by van der Waals forces, and enhances the diffusion capacity of water molecules in the composite film. At the same time, the doping of fullerol significantly increases the water molecule adsorption sites on the surface of the composite material, and its abundant hydroxyl functional groups greatly enhance the hydrophilicity of the composite film, further enhancing the wet-sensitive performance of the sensor. This sensor uses a high-baseband patch-type QCM as a transducer, and only requires a trace amount of hygroscopic material to achieve excellent hygroscopic response, and exhibits a small hygroscopic effect and fast response / recovery characteristics. The ultra-sensitive QCM humidity sensor can be used to detect the evaporation of sweat in the palm and back of the hand wearing a breathable glove, and then identify the palm and back of the hand by distinguishing the difference between the two evaporation conditions. Compared with vision-based sensors, the QCM humidity sensor mentioned in the present invention is less sensitive to ambient light fluctuations during the recognition process, so the recognition ability is more stable in an environment with complex and changeable light. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a structural schematic diagram of the ultra-sensitive humidity sensor in the present invention;

[0033] Figure 2 It is a transmission electron microscope image of the pure Ti3C2Tx film in the present invention;

[0034] Figure 3 This is a transmission electron microscope image of a fullerol / Ti3C2Tx composite film prepared by using a 5wt% fullerol / Ti3C2Tx composite solution in the present invention;

[0035] Figure 4 The frequency response diagrams of the ultra-sensitive humidity sensor at different humidity levels obtained for Examples 1-3 and Comparative Examples 1-2 of the present invention;

[0036] Figure 5 This is a frequency response diagram of the ultra-sensitive humidity sensor prepared by using 5wt% fullerene alcohol / Ti3C2Tx composite solution in the humidification and dehumidification process in the present invention;

[0037] Figure 6 This is a response / recovery time result diagram of the ultra-sensitive humidity sensor prepared by using 5 wt % fullerene alcohol / Ti3C2Tx composite solution in the present invention;

[0038] Figure 7 A schematic diagram of using the ultra-sensitive humidity sensor of the present invention to detect the evaporation of sweat in the palm and back of the hand wearing a breathable glove;

[0039] Figure 8 This is a result diagram of using the ultra-sensitive humidity sensor of the present invention to detect the evaporation of sweat in the palm and back of the hand wearing a breathable glove;

[0040] Explanation of the reference numerals: 1-quartz wafer, 2-lower electrode, 3-upper electrode, 4-fullerol / Ti3C2Tx composite film, 41-fullerol, 42-Ti3C2Tx. DETAILED DESCRIPTION

[0041] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.

[0042] Example 1

[0043] A QCM sensor includes a high fundamental frequency QCM substrate, on which a fullerol / Ti3C2Tx composite film 4 is disposed. In this embodiment, the fullerol 41 is a fullerol produced by Jiangsu Xianfeng Nanomaterial Technology Co., Ltd. with a model number of XFC00-6, a hydroxyl number of 18-28, and prepared by an arc method; the Ti3C2Tx 42 is a Ti3C2Tx with a model number of MK4802, a sheet diameter of 0.2-10 μm, and a single-layer structure produced by Nanjing Muke Nanotechnology Co., Ltd. The high fundamental frequency QCM substrate is a patch-type QCM, and the reference frequency is 19.6 MHz, such as Figure 1 As shown, the high fundamental frequency QCM substrate is composed of a quartz wafer 1 and a lower electrode 2 and an upper electrode 3 arranged on the quartz wafer 1. In this embodiment, the size of the high fundamental frequency QCM substrate is 4*2mm 2 .

[0044] A method for preparing a QCM sensor, comprising:

[0045] S1: Preparation of fullerol / Ti3C2Tx composite dispersion solution;

[0046] S11: 50 mg of fullerol powder was added to 10 mL of deionized water, and ultrasonic stirring was performed for 30 minutes to prepare a fullerol solution with a concentration of 5 mg / mL;

[0047] S12: 50 mg Ti3C2Tx powder was ultrasonically dispersed in 10 mL deionized water to prepare a Ti3C2Tx solution with a concentration of 5 mg / mL;

[0048] S13: mixing the Ti3C2Tx solution and the fullerol solution in a mass ratio of 1:0.05 to form a 5 wt% fullerol / Ti3C2Tx composite solution;

[0049] S2: Take 0.2 μL of the fullerol / Ti3C2Tx composite solution prepared in step 3 and apply it by drop coating to the surface of the upper electrode layer 3 of the substrate of a small-sized patch-type QCM with a reference frequency of 19.6 MHz, and dry it in nitrogen for 10 hours to obtain a high-base frequency QCM substrate coated with the fullerol / Ti3C2Tx composite film 4. The sensor is named Sensor3.

[0050] The transmission electron microscopy images of the pure Ti3C2Tx thin film and the fullerol / Ti3C2Tx composite film prepared by using 5wt% fullerol / Ti3C2Tx composite solution in this embodiment are shown in FIG. Figure 2 and Figure 3 As shown, from Figure 3 It can be seen from the difference that fullerol 41 is evenly distributed on the surface and interlayer of Ti3C2Tx 42.

[0051] Under normal atmospheric pressure and room temperature (about 25°C), the frequency response test of the ultra-sensitive humidity sensor prepared by using 5wt% fullerol / Ti3C2Tx composite solution was carried out at different humidity levels from 2%RH to 97%RH. The results are as follows: Figure 4 As shown, the sensor has an ultra-high frequency response with a maximum frequency deviation of approximately 13kHz.

[0052] Under normal atmospheric pressure and room temperature (about 25°C), the frequency response test of the ultra-sensitive humidity sensor prepared by using 5wt% fullerol / Ti3C2Tx composite solution was carried out when the humidity gradually increased from 2%RH to 97%RH and then gradually decreased to 2%RH. Figure 5 As shown, the sensor exhibits less hysteresis.

[0053] Under normal atmospheric pressure and room temperature (about 25° C.), the ultra-sensitive humidity sensor in this embodiment was tested for response / recovery time when the humidity was switched from 2% RH to 84% RH. Figure 6 As shown, the sensor exhibits a faster response / recovery speed.

[0054] Example 2

[0055] This embodiment is substantially the same as embodiment 1, except that the mass ratio of Ti3C2Tx to fullerene alcohol is 1:0.02. The sensor obtained in this embodiment is named Sensor 2.

[0056] Example 3

[0057] This embodiment is substantially the same as embodiment 1, except that the mass ratio of Ti3C2Tx to fullerene alcohol is 1:0.08. The sensor obtained in this embodiment is named Sensor 4.

[0058] Example 4

[0059] This embodiment is basically the same as Embodiment 1, except that the amount of the Ti3C2Tx / fullerol composite solution used is 0.5 μL.

[0060] Example 5

[0061] This embodiment is basically the same as Embodiment 1, except that the amount of fullerol / Ti3C2Tx composite solution used is 1 μL.

[0062] Comparative Example 1

[0063] This comparative example is substantially the same as Example 1, except that no fullerol is added. The sensor obtained in this comparative example is named Sensor 1.

[0064] Comparative Example 2

[0065] This comparative example is basically the same as Example 1, except that 5 wt% of the fullerol / Ti3C2Tx composite solution is coated on the upper electrode surface of the QCM substrate with a reference frequency of 10 MHz. The sensor obtained in this comparative example is named Sensor 5.

[0066] Comparative Example 3

[0067] This comparative example is basically the same as Example 1, except that the amount of fullerol / Ti3C2Tx composite solution used is 0.05 μL.

[0068] Comparative Example 4

[0069] This comparative example is basically the same as Example 1, except that the amount of fullerol / Ti3C2Tx composite solution used is 2 μL.

[0070] Comparative Example 5

[0071] This comparative example is basically the same as Example 1, except that a multi-layer Ti3C2Tx (5 to 10 layers) is used instead of a small layer Ti3C2Tx.

[0072] Under normal atmospheric pressure and room temperature (about 25°C), the sensors obtained in Examples 1-3 and Comparative Examples 1-2 were tested for frequency response at different humidity levels from 2% RH to 97% RH. The results are as follows: Figure 4 As shown in the figure, the high fundamental frequency (19.6MHz) QCM sensor (Sensor 3) coated with a proper mass ratio (5wt%) of fullerol / Ti3C2Tx composite film has an ultra-high frequency response, with a maximum frequency shift of about 13kHz. Compared with the low fundamental frequency (10MHz) QCM sensor (Sensor 5) coated with the Ti3C2Tx / fullerol composite film with the same proper mass ratio (5wt%) and the high fundamental frequency (19.6MHz) QCM sensor (Sensor 1) coated with pure Ti3C2Tx film, the frequency response of the sensor to humidity is greatly improved.

[0073] The performance of the sensors obtained in the above examples 1-5 and comparative examples 1-5 was tested, and the obtained data are shown in Table 1:

[0074] Table 1

[0075]

[0076] As can be seen from Table 1, compared with Comparative Example 1 (Sensor 1), the sensors in Examples 1-3 (Sensor 2-4) significantly improved the humidity response performance by introducing fullerol. As the fullerol content increases, the response of the sensor also increases. In particular, when the fullerol content increases to 5wt%, the frequency shift of Sensor 3 reaches a maximum value of -12.8kHz, which is almost twice that of Sensor 1. However, if the fullerol content increases to 8wt%, the humidity sensing performance of the sensor will be reduced. In addition, compared with the QCM sensor coated with the same material but with a lower fundamental frequency (Comparative Example 2, Sensor 5), its maximum frequency shift is only -1.3kHz. It is worth noting that the amount of fullerol / Ti3C2Tx composite solution dripped on the high fundamental frequency QCM substrate also has a significant effect on the performance of the sensor. If the drip amount is too small (Comparative Example 3), the sensitivity of the sensor will be insufficient. On the contrary, if the amount of drop coating is too much (Example 4, Example 5, Comparative Example 4), the response and recovery speed of the sensor will be reduced. In addition, if the number of layers of Ti3C2Tx is too thick (Comparative Example 5), it will hinder the diffusion of water molecules, which will not only reduce the sensitivity of the sensor, but also slow down the response and recovery speed. The above results show that the right amount of fullerol plays a key role in improving the overall humidity-sensitive performance of Ti3C2Tx, and increasing the fundamental frequency of the QCM device is an effective way to enhance the sensitivity of the sensor.

[0077] Example 4

[0078] An application of a QCM sensor in identifying the palm and back of a hand wearing a glove. In this embodiment, the gloves are cotton breathable gloves. The ultra-sensitive humidity sensor in Example 1 is used to detect the sweat evaporation of the palm and back of the hand wearing the breathable gloves. The detection schematic diagram is shown in FIG. Figure 7 The test results are shown in the figure Figure 8 As shown, Figure 8 The test results in show that the sensor has a good detection effect on the sweat evaporation of the palm and back of the hand wearing breathable gloves. The palm and back of the hand can be identified by distinguishing the frequency response values ​​of the sensor in different areas. Compared with the vision-based sensor, the QCM humidity sensor mentioned in this embodiment is less sensitive to ambient light fluctuations during the recognition process, so the recognition ability is more stable in an environment with complex and changing light.

[0079] The above-mentioned embodiments only express the specific implementation methods of the present application, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the protection scope of the present application. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the technical solution concept of the present application, and these all belong to the protection scope of the present application.

Claims

1. A QCM sensor, characterized in that: The invention comprises a high fundamental frequency QCM substrate, wherein the high fundamental frequency QCM substrate comprises a quartz wafer (1) and an upper electrode layer (3) and a lower electrode layer (2) respectively arranged on the upper and lower surfaces of the quartz wafer (1); a fullerol / Ti3C2Tx composite film (4) is arranged on the surface of the upper electrode layer (3); and fullerol (41) is dispersed on the surface and between the Ti3C2Tx (42) in the fullerol / Ti3C2Tx composite film (4).

2. A QCM sensor according to claim 1, characterized in that: The particle size of the fullerol (41) in the fullerol / Ti3C2Tx composite film (4) is 1 to 100 nm, and the number of hydroxyl groups is 15 to 40.

3. A QCM sensor according to any one of claims 1-2, characterized in that: The number of layers of Ti3C2Tx (42) in the fullerol / Ti3C2Tx composite film (4) is 1 to 5, and the sheet diameter is 0.2 to 10 μm.

4. A QCM sensor according to any one of claims 1-2, characterized in that: The high base frequency QCM substrate is a patch type QCM, and the base frequency is 15MHz to 40MHz.

5. A method for preparing a QCM sensor, characterized in that: include: S1: Preparation of fullerol / Ti3C2Tx composite dispersion solution; S2: Coat the prepared fullerol / Ti3C2Tx composite dispersion solution on the surface of the high fundamental frequency QCM substrate to form a fullerol / Ti3C2Tx composite film (4), thereby obtaining the QCM sensor according to any one of claims 1 to 4.

6. The method for preparing a QCM sensor according to claim 5, characterized in that: The specific steps of S1 are as follows: S11: preparing a fullerol solution with a concentration of 0.1 to 10 mg / mL by mixing fullerol powder with water; S12: preparing a Ti3C2Tx solution with a concentration of 0.1 to 10 mg / mL by mixing Ti3C2Tx powder with water; S13: The Ti3C2Tx solution and the fullerol solution are mixed in a mass ratio of 1:(0.01-10) to form a fullerol / Ti3C2Tx composite dispersed solution with a concentration of 0.1-10 mg / mL.

7. The method for preparing a QCM sensor according to claim 5, characterized in that: The dosage of the fullerol / Ti3C2Tx composite dispersion solution is 0.0125-0.125 μL / mm 2 , and the amount of fullerol / Ti3C2Tx composite dispersion solution increases with the increase of the surface area of ​​the high fundamental frequency QCM substrate.

8. Use of the QCM sensor according to any one of claims 1 to 4 in identifying the palm and back of a hand wearing a glove.

9. The use of the QCM sensor according to claim 8 in identifying the palm and back of a hand wearing a glove, characterized in that: The gloves are breathable gloves.

10. The use of the QCM sensor according to claim 9 in identifying the palm and back of a hand wearing a glove, characterized in that: The following steps are involved: A1: Using the QCM sensor as described in any one of claims 1 to 4 close to the palm and back of the hand wearing the glove; A2: The QCM sensor is used to detect the evaporation of sweat on the palm and back of the hand wearing the glove, and the palm and back of the hand are identified by distinguishing the difference in sweat evaporation.